The marquess and the runaway lady - Hastings, Samantha (Harlequin historicals., 2023)
"When the Marquess of Cheswick--Wick--takes in a mysterious woman, he's shocked to discover she is Lady Louisa, an heiress who's escaped her cruel aunt! Grieving the loss of two siblings, Wick avoids opening his heart to anyone else and stays away from the marriage mart. But when Louisa needs a husband in order to claim her inheritance, Wick's determined to help--even if it means stepping back into his worst nightmare: the Season!"--Back cover.